Prospective 2035 for the dairy agroindustrial chain: using the Delphi approach and scenario methodology - Sossa, Jhon Wilder Zartha; Monsalve, Adriana Maria Zuluaga; Posada, Nolberto Gutiérrez; Montoya, Luis Horacio Botero; Piedrahíta, Juan Carlos Palacio; Mendoza, Gina Lía Orozco; Sarta, John Fredy Moreno; Grisales, Liliana Valencia; López, Camilo Andrés Grajales (Frontiers in Sustainable Food Systems, 2025)
The objective of this article is to identify and prioritize technologies, innovations and new businesses related to the dairy agro-industrial chain that are expected to emerge by 2035. To do so, the two-round Delphi method was used and questionnaires were applied to 27 national and international experts. A technology tree was built with Python codes and libraries, consisting of 174 topics. Additionally, 39 variables were generated for scenarios in the Good Livestock Practices BPG; Research, Development and Innovation R&D&I; Sustainable Livestock and Agroindustry groups, as well as four hypotheses and a bet scenario, with the future objectives of sustainable specialization of forage production and mass production and standardization in collection centers. This can be achieved through projects on technologies and innovations prioritized in the Delphi method, including ultrasound, pulsed combustion drying, dairy-derived medicinal products, bioethanol produced from whey, artificial intelligence and selection assisted by molecular markers, electromembrane filtration technologies, whey protein concentrates, life cycle assessment, blockchain, neural networks and smart assays, among others. The opportunity that actors in the Science, Technology and Innovation system have in the chain for the development of programs, plans, public policies and open innovation challenges in the prioritized technologies is highlighted.